From Bench to Bed, Back and Beyond: The Four Bs of Biomedical Research - Neresini, Federico; Viteritti, Assunta (Tecnoscienza – Italian Journal of Science & Technology Studies, 2014)
Contemporary biomedicine is characterized by the ever-closer connection between clinical practice and research. Laboratories become nodes of articulated networks, making it no longer possible to consider them as single entities. In light of these changes, a wide range of actors – researchers, scientific instruments, data-bases, experts in bio-informatics and bio-statistics, pharmaceutical companies, clinicians, drugs, patients, cells, ethical and regulatory issues – are involved. In this Introduction, we address why these processes represent a relevant challenge for social sciences as well.